In vitro Anthelmintic Activity of Seeds of Cicer arietinum Linn. - Kumar, Praveen; Solanki, Ruchi; Tripathi, Laxmi (Asian Journal of Chemistry, 2013)
Methanolic extract of seeds of Cicer arietinum Linn. was tested for anthelmintic activity against indian earthworm (Pheretimaposthuma), roundworm (Ascaridia galli) and tapeworms (Raillietina spiralis). Various concentrations of extract were tested and results were expressed in terms of time for paralysis and time taken for death of worms and helminths. Dose dependent activity was observed in the methanolic extract of Cicer arietinum Linn. may be useful as an anthelmintic.